(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
This paper uses a systematic literature review as means of investigating the rigor of claims arising from Web engineering research. Rigor is measured using criteria combined from software engineering research. We reviewed 173 papers and results have shown that only 5% would be considered rigorous methodologically. In addition to presenting our results, we also provide suggestions for improvement of Web engineering research based on lessons learnt by the software engineering community